Accontability of a Notary Public Credit Agreement Signing Process - Octovindo Baharano (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The role of a notary in making a bank credit agreement deed is very important in making a credit agreement deed. The purpose of this study is to determine and analyze the validity of a bank credit agreement and the accountability of a notary to the parties if the credit agreement signing process cannot be carried out in accordance with Act No. 2 of 2014 concerning Amendments to the Laws and Regulations Number 30 of 2004. regarding the Position of Notary Public. The approach to the problem that will be used in this thesis is a normative juridical approach. The validity of a bank credit agreement is adjusted to the legal terms of the agreement according to Article 1320 of the Civil Code, namely agreement, competence, lawful causes, and certain matters. The form and format shall be submitted by Bank Indonesia to the respective bank to determine it, however in safeguarding measures, at least it must pay attention to the following matters: Fulfilling the legality and legal requirements that can protect bank interests and Contain the amount, period, procedure repayment of credit and other credit terms as stipulated in the said credit approval decision. The responsibility of a notary is only limited to the process of implementing the credit agreement, only to the actions taken whether it is in accordance with the procedure or not, not to the administrative nature. Fulfills the legality and legal requirements that can protect the interests of the bank and contains the amount, period, procedure for repayment of credit and other credit requirements as stipulated in the credit approval decision. The responsibility of a notary is only limited to the process of implementing the credit agreement, only to the actions taken whether it is in accordance with the procedure or not, not to the administrative nature. Fulfills the legality and legal requirements that can protect the interests of the bank and contains the amount, period, procedure for repayment of credit and other credit terms as stipulated in the credit approval decision. The responsibility of a notary is only limited to the process of implementing the credit agreement, only to the actions taken whether it is in accordance with the procedure or not, not to the administrative nature.